Temporomandibular Dysfunction and Oral Parafunctions in Late Adolescence - Liset María Frías Figueredo; Deneb Nerey Arango; Ileana Grau León; Rogelio Cabo García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Background: Temporomandibular dysfunction is a pathological entity related to functional problems that affect the temporomandibular joint and / or the masticatory muscles and associated structures. Its frequency tends to increase during puberty. Objective: To determine the frequency of temporomandibular dysfunction and its association with the presence of oral parafunctional in students from 16 to 18 years old. Methods: A descriptive study was conducted including 86 students from 16 to 18 years old who were studying at Robert Labrada Águila high school from September to November 2010. Helkimo index was applied in order to determine temporomandibular dysfunction frequency. Sociodemographic variables were also assessed and the presence of oral parafunctional habits as detected during physical examination. Results: 69.8% of respondents presented some level of temporomandibular dysfunction. Bruxism was the parafunction that mostly related to the initiation and development of temporomandibular dysfunction. Conclusions: There was a high frequency of temporomandibular dysfunction in this population.